2022
DOI: 10.3390/cancers14061561
|View full text |Cite
|
Sign up to set email alerts
|

Interrogating the Genomic Landscape of Uterine Leiomyosarcoma: A Potential for Patient Benefit

Abstract: Uterine leiomyosarcoma (uLMS) is a rare and aggressive gynaecological malignancy. Surgical removal and chemotherapy are commonly used to treat uLMS, but recurrence rates are high. Over the last few decades, clarification of the genomic landscape of uLMS has revealed a number of recurring mutations, including TP53, RB1, ATRX, PTEN, and MED12. Such genomic aberrations are difficult to target therapeutically or are actively targeted in other malignancies, and their potential as targets for the treatment of uLMS r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 205 publications
1
10
0
Order By: Relevance
“…First, our ndings are in accordance with others when characterizing biomarkers in uLMS including HRD, low TMB, low MSI, and features of immunologically cold tumors (5,6,9,10,21).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…First, our ndings are in accordance with others when characterizing biomarkers in uLMS including HRD, low TMB, low MSI, and features of immunologically cold tumors (5,6,9,10,21).…”
Section: Discussionsupporting
confidence: 91%
“…In recent years, the identi cation of variants has emerged as a promising avenue for identifying novel diagnostic and therapeutic targets in uLMS (5,6). Characterizing the molecular landscape of uLMS is essential for the development of targeted therapies, but the molecular underpinnings of this tumor are complex and the identi cation of actionable targets is challenging (7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…RNA sequencing has also identified frequent fusion genes disrupting multiple tumour suppressor genes, such as RB1, TP53, ATRX, DAXX, CAMTA1, SETD2 and KDM5CA [ 14 ]. Currently, none of these aberrations are routinely targeted therapeutically in individuals with uLMS [ 18 ] and thus treatment strategies continue unchanged and disease outcomes have remained stagnant for decades.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike individuals with other gynaecological malignancies, who are typically referred to familial genetics clinics for germline BRCA1/2 testing, individuals with uLMS are not routinely screened for such germline mutations in the clinic, although some individuals with uLMS have been shown to carry germline mutations in TP53 or RB1 [ 18 ], albeit at a low rate (below the internationally accepted cut off of ~ 10% prevalence for germline mutations in the target population requiring testing [ 27 ]). In their reanalysis of the TCGA and GENIE soft-tissue sarcoma datasets, in addition to their own uLMS cohort, Seligson and associates observed that alterations in BRCA1/2 , concluded to be somatic, were significantly more common in uLMS compared with non-uterine LMS (10% compared to 1%, respectively, p -value 0.02, n = 61 patients) [ 28 ].…”
Section: Introductionmentioning
confidence: 99%